2023
DOI: 10.3389/fpls.2023.1232271
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing indigenous plant growth promoting bacteria and their synergistic effects with organic and chemical fertilizers on wheat (Triticum aestivum)

Israr Asghar,
Maqsood Ahmed,
Muhammad Ansar Farooq
et al.

Abstract: The excessive use of chemical fertilizers is deteriorating both the environment and soil, making it a big challenge faced by sustainable agriculture. To assist the efforts for the solution of this burning issue, nine different potential native strains of plant growth-promoting bacteria (PGPB) namely, SA-1(Bacillus subtilis), SA-5 (Stenotrophomonas humi),SA-7(Azospirillum brasilense), BH-1(Azospirillum oryzae), BH-7(Azotobacter armeniacus), BH-8(Rhizobium pusense), BA-3(Azospirillum zeae), BA-6(Rhizobium pusens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 103 publications
2
2
0
Order By: Relevance
“…The study confirms the positive effect of glauconite on soil characteristics, which agrees with the findings of I. Asghar et al (2023), which shows an increase in the content of major nutritional elements and humic substances in the soil. This indicates that the addition of glauconite does improve soil fertility and stimulate plant growth.…”
Section: Discussionsupporting
confidence: 90%
“…The study confirms the positive effect of glauconite on soil characteristics, which agrees with the findings of I. Asghar et al (2023), which shows an increase in the content of major nutritional elements and humic substances in the soil. This indicates that the addition of glauconite does improve soil fertility and stimulate plant growth.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, there exists a significant positive correlation between soil nutrients and plant growth as documented in previous studies [20,53,54]. This is in accordance with the research conducted by Asghar et al [55] wherein various PGPB they identified demonstrated increased wheat yield, improved nutritional and quality parameters, and enhanced availability of soil nutrients when employed in conjunction with organic and chemical fertilizers.…”
Section: Discussionsupporting
confidence: 88%
“…These bacteria can act as biofertilizers through various mechanisms, including nitrogen fixation, nutrient solubilization, ammonium production, siderophore production and hormone production. Consequently, the use of PGPB can enhance plant nutrient uptake ( Ijaz et al., 2021 ; Tsegaye et al., 2022 ) and increase the efficiency of synthetic fertilization ( Mortinho et al., 2022 ; Asghar et al., 2023 ). The PGPB communities have great potential to reduce the dependency on synthetic fertilizers, such as nitrogen, phosphorus, and potassium, in both soil ( Rosa et al., 2022 ; Tounsi-Hammami et al., 2022 ) and soilless conditions ( Ikiz et al., 2024 ).…”
Section: Introductionmentioning
confidence: 99%